On Dobrushin Ergodicity Coefficient and weak ergodicity of Markov Chains on Jordan Algebras - Mukhamedov, Farrukh (Institute of Physics Publishing, 2013)
In this paper we study certain properties of Dobrushin's ergodicity coecient for stochastic operators dened on non-associative L1-spaces associated with semi-nite JBW- algebras. Such results extends the well-known classical ones to a non-associative setting. This allows us to investigate the weak ergodicity of nonhomogeneous discrete Markov processes (NDMP) by means of the ergodicity coecient. We provide a necessary and sucient conditions for such processes to satisfy the weak ergodicity.